2013
DOI: 10.1016/j.rmed.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis infection among healthcare workers: Risk factors and 20-year evolution

Abstract: Incidence of LTBI among HCWs is high, although it decreased throughout the follow-up period. It is crucial to maintain surveillance programs in HCWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
(17 reference statements)
2
15
0
2
Order By: Relevance
“…Our study demonstrated that, although there is an association between the risks of a positive TST or IGRA with a working exposure, this risk was not associable with working in high-risk areas; as previously described, some authors found an association with working in wards, as emergency department, where undiagnosed patients are seen [24]. …”
Section: Discussionsupporting
confidence: 70%
“…Our study demonstrated that, although there is an association between the risks of a positive TST or IGRA with a working exposure, this risk was not associable with working in high-risk areas; as previously described, some authors found an association with working in wards, as emergency department, where undiagnosed patients are seen [24]. …”
Section: Discussionsupporting
confidence: 70%
“…cough-inducing procedures, myobacteriology or pathology laboratory work [16]. They were assumed to have a 4.4% annual probability of exposure to contagious TB, corresponding to the ‘moderate-risk’ group described by Salpeter et al in 2004 [17], and reflecting more recent incidence data reported by Lambert et al in 2012 [12].…”
Section: Methodsmentioning
confidence: 99%
“…Since our focus was HCWs at risk of developing TB infection, we did not consider the lowest-risk workers, clerical, maintenance and laundry employees [16]. Similarly, we assumed that all HCWs in the cohort worked in hospitals where TB patients were likely to be admitted (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A longer period of employment as health professional, patient's delayed diagnosis of the disease, professional category certain work locations such as inpatient TB facility laboratory, internal medicine, and emergency facilities in addition to the lack of proper respiratory protection (N95 masks), are factors that can contribute to the infection. 25 TB is more prevalent in the young adult working-age population than in the general population. 26 Although most studies do not specify a relation between the development of TB and the mean age in HCW and non-HCW, our findings show that among those occupationally-acquired TB, those who were 43 years or older with greater, were…”
Section: 17mentioning
confidence: 97%